Dual‐Functional Photocatalysis for Cooperative Hydrogen Evolution and Benzylamine Oxidation Coupling over Sandwiched‐Like Pd@TiO2@ZnIn2S4 Nanobox. Issue 10 (5th January 2022) - She, Ping; Qin, Jun‐sheng; Sheng, Jiyao; Qi, Yuanyuan; Rui, Hongbang; Zhang, Wei; Ge, Xin; Lu, Geyu; Song, Xiaowei; Rao, Heng
Abstract: Photocatalytic hydrogen evolution (PHE) over semiconductor photocatalysts is usually constrained by the limited light‐harvesting and separation of photogenerated electron–hole pairs. Most of the reported systems focusing on PHE are facilitated by consuming the photoinduced holes with organic sacrificial electron donors (SEDs). The introduction of the SEDs not only causes the environmental problem, but also increases the cost of the reaction. Herein, a dual‐functional photocatalyst is developed with the morphology of sandwiched‐like hollowed Pd@TiO2 @ZnIn2 S4 nanobox, which is synthesized by choosing microporous zeolites with sub‐nanometer‐sized Pd nanoparticles (Pd NPs) embedded as the sacrificial templates. The ternary Pd@TiO2 @ZnIn2 S4 photocatalyst exhibits a superior PHE rate (5.35 mmol g −1 h −1 ) and benzylamine oxidation conversion rate (>99%) simultaneously without adding any other SEDs. The PHE performance is superior to the reported composites of TiO2 and ZnIn2 S4, which is attributed to the elevated light capture ability induced by the hollow structure, and the enhanced charge separation efficiency facilitated by the ultrasmall sized Pd NPs. The unique design presented here holds great potential for other highly efficient cooperative dual‐functional photocatalytic reactions. Abstract : A dual‐functional photocatalyst with the morphology of sandwiched‐like hollowed Pd@TiO2 @ZnIn2 S4 nanobox is developed, which is synthesized by choosing microporous zeolites with sub‐nanometer‐sized Pd nanoparticles embedded as the sacrificial templates. The ternary Pd@TiO2 @ZnIn2 S4 photocatalyst exhibits a superior photocatalytic hydrogen evolution rate and benzylamine oxidation conversion rate simultaneously without adding any other sacrificial electron donors.